The diseased city. The hospital of Tunja and its miasmas (1777-1822) (2021)
This article studies the impact of the Bourbon Reforms on the hospital of Tunja, in the viceroyalty of New Granada, between the end of the 18th century and the first decades of the 19th century. Through the analysis of archival sources and a critical reading of secondary sources, the sanitary problem caused by the transfer of the hospital to a corner of the main square of Tunja is reconstructed. The confrontations between the religious orders, secular clergy and neighbours, represented by the town council and the Temporalities Committee, the Royal Court and the Viceroy of Santafé (Bogotá), were caused by the miasma produced from the infirmaries, latrines and cemetery of the convent-hospital and the miasmatic explanations for and against its transfer. The Bourbon Reforms had particularities in regional contexts, such as the one under study, which makes it possible to differentiate between the reforms in the medical and health fields and those applied to religious orders in fulfilment of the Royal Patronage and regalian control of charitable hospital institutions. Finally, it was the Republic that decided on the transfer of the hospital, and resolved the problem caused by the miasmas, and took administrative control of its revenue, displacing and extinguishing the Hospitaller Order.